1996
DOI: 10.5326/15473317-32-1-77
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal laminectomy in the treatment of cervical intervertebral disk disease in small dogs: a retrospective study of 30 cases

Abstract: Dorsal laminectomy was used to treat 30 dogs with cervical intervertebral disk disease. A variety of breeds were represented, and all animals weighted 15 kg or less. Myelography was utilized to locate each solitary disk herniation. All 30 cases progressed to complete recovery which indicates that dorsal laminectomy may be performed with success in small dogs with intervertebral disk disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 0 publications
3
27
0
10
Order By: Relevance
“…This data is in agreement with past reports [4,8,11]. The degree of neurological deficit of the dogs in the C-IVDH group included in this study is in close agreement with that found in a previous retrospective study of IVDH in that grades 3, 2 and 1 made up 17%, 30% and 53% of the study population, respectively [11]. The characteristics of the disease in the predominant dog breeds in the C-IVDH group in Japan, the Beagle, Dachshund and Shih Tzu, were analyzed.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This data is in agreement with past reports [4,8,11]. The degree of neurological deficit of the dogs in the C-IVDH group included in this study is in close agreement with that found in a previous retrospective study of IVDH in that grades 3, 2 and 1 made up 17%, 30% and 53% of the study population, respectively [11]. The characteristics of the disease in the predominant dog breeds in the C-IVDH group in Japan, the Beagle, Dachshund and Shih Tzu, were analyzed.…”
Section: Discussionsupporting
confidence: 83%
“…The rate of this disorder in the Beagle is clearly larger in Japan than in other countries, and this may reflect the Beagle breeding rate in Japan. Age at admission in this study was in agreement with previous data that indicated a range of 7.4 to 8.2 years of age [4,8,11,28]. In the current study, females made up 37.1% of the C-IVDH group and males made up the other 62.9%, and these results indicate that male dogs are almost twice as likely as females to suffer C-IVDH.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…other studies have reported more favourable outcomes with limited hospitalisation and 60 recovery times (Gill et al, 1996;Faissler, 2011, De Decker et al, 2012a Further information recorded included signalment, bodyweight, duration of clinical signs 82 prior to surgery (acute <48 h, subacute 2-7 days and chronic >7 days), diagnosis, type, 83 location, extent (number of vertebrae operated on) and duration of the surgery, presence of 84 perioperative complications during the period of hospitalisation and hospitalisation time. (Table 2).…”
mentioning
confidence: 99%